Determination of Building Mortar Mixers Effectiveness - Rohozin, Ivan; Vasyliev, Oleksiy; Pavelieva, Anna (International Journal of Engineering and Technology, 2018)
The peculiarities of building mortar mixes preparation in cyclic compulsory mixers of various designs have been considered in this article. The work of mixers with a horizontal shaft, a vertical shaft, beaters, screw straps, as well as planetary motion of mixing stars with beaters have been described in detail. The main attention here is paid to the constructive performance of machinery. A relative assessment is given to the manual bearing groups. The multi-purpose system of numerical indices necessary for the performance assessment of mixersâ€™ running efficiency is proposed and defined in this paper. The design of the mixers is considered in this research according to the number of components of the mixture particles motion, which arise from the constrained influence of the movable operating element. The indicators of net weight and area in the plan are attributed to the productivity. The general method of determining the coefficient for assessing the impact, exerted by the design of the mixers on their running efficiency, has also been developed by the authors of this scientific investigation. The obtained data will enable to investigate and improve the design of the mixers, finding the ways to increase their working efficiency.Â Â